Construction of antibiotic-induced depression mice model and the function of intestinal microbiota - Deng, Handan; Yu, Yongjun; Sha, Qi; Sun, Weiyi; Liang, Lundan; Ren, Feier; Ji, Hua; Shen, Xiangdi; Fan, Xingli (Frontiers in Microbiology, 2023)
There are many researches focus on intestinal microbiota-related depression induced by the usage of antibiotics, but the use of antibiotics is pretty different. In order to construct an effective antibiotic-induced depression mice model and explore the effect of intestinal microbiota in antibiotic-induced depression, we used several kinds of antibiotic mixtures to induce mice depression and used depression-related behavioral tests and neurobiological factors to evaluate the construction of the antibiotic-induced depression mice model. SPSS statistical software was used to analyze the above data, and the optimal model was selected according to the stability of the results and the simplicity of modeling methods. Metagenomics analysis and fecal microbiota transplantation (FMT) of intestinal microbiota from antibiotic-induced depression mice were performed to analyze the effect of intestinal microbiota. The results showed antibiotics mixture A (1.25ug/ml natamycin, 5mg/ml neomycin sulfate and 5mg/ml bacitracin), antibiotics mixture B (24mg/ml bacitracin, 24mg/ml neomycin sulfate, 9.6mg/ml ampicillin, 4.8mg/ml meropenem and 1.47mg/ml vancomycin) and antibiotic solution D (only containing 5mg/ml neomycin sulfate) could induce depression-like behavior in mice. By using these antibiotics, the concentrations of norepinephrine (NE), 5-Hydroxytryptamine (5-HT) and brain-derived neurotrophic factor (BDNF) in mice hippocampus and prefrontal cortex tissues were significantly decreased. All the above results were consistent with those of chronic unpredictable mild stress (CUMS) depression mice.The FMT results showed fecal microbiota from antibiotic-induced depressed mice transplanted into normal mice (8-week-old male C57BL/6J SPF mice) also could induce depression-like behavior and cause the similar changes of neurobiological factors. Metagenomics analysis showed that community structure of microbiota in the intestinal tract of antibiotic-induced depression mice was significantly different from that in control mice, the intestinal microbiota species diversity in antibiotic-induced depression mice was lower, the lipoic acid metabolism pathway was significantly activated, the abundance of functional gene lipA was explicitly increased. Quantitative real-time PCR (qPCR) further verified the abundance of enriched bacteria in the intestinal microbiota of antibiotic-induced depression mice. In summary, the specific antibiotic mixtures can induce depression by causing changes of intestinal microbiota in mice. Antibiotic-induced depressed mice show differences in intestinal microbiota abundance, high enrichment of the unique metabolic pathway and the functional gene.